2020
DOI: 10.1051/bioconf/20202003005
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Fungal Endophyte Penicillium citrinum on Tree Seedling: Applicability and Limitation

Abstract: Penicillium citrinum is an endophyte fungus isolated from plant tissues that live in tropical peatland. Various study reveals that endophytic fungi give advantages to plant health. Since 2015, series of experiments were conducted to investigate the capability of P. citrinum P3.10 as biofertilizer of plant tree in nursery stage which are: pathogenicity test, in vitro assay, direct application to seeds, dosage test, and fertilizer formulation. This paper presents a review from our research of P. citrinum isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(15 reference statements)
1
0
0
1
Order By: Relevance
“…Our results showed a significant increase in water content, dry mass, photosynthetic pigments, some osmolytes and enzymatic antioxidants. These findings are consistent with those of [67]. This study found that many endophytic fungi might significantly boost the root-dry biomass of maize at higher Zn and Cd contents.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed a significant increase in water content, dry mass, photosynthetic pigments, some osmolytes and enzymatic antioxidants. These findings are consistent with those of [67]. This study found that many endophytic fungi might significantly boost the root-dry biomass of maize at higher Zn and Cd contents.…”
Section: Discussionsupporting
confidence: 92%
“…Avila-Diaz et al (2013) juga melaporkan bahwa P. citrinum juga ditemukan pada anggrek epifit Laelia speciosa (HBK) Schltr asal Meksiko. Beberapa peran P. citrinum diantaranya ialah menghasilkan giberelin dan sitokinin (Gu et al 2023), meningkatkan penyerapan nutrisi dan pertumbuhan tanaman (Hakim & Yuwati 2020), memproteksi tanaman terhadap cekaman biotik (Waqas et al 2015), serta memproduksi senyawa anticendawan dan antimikrob lainnya yang bermanfaat dalam bidang pertanian, farmasi, dan bioteknologi. Penicilium citrinum juga berpotensi sebagai antikanker, antivirus, antioksidan dan antiinflamasi (Toghueo & Boyom 2020).…”
Section: Pembahasanunclassified